Process philosophy and political liberalism : rawls, whitehead, hartshorne - Dombrowski, Daniel A. (Edinburgh University Press, 2019)
Daniel A. Dombrowski brings together the thought of the 20th-century philosophy's greatest political liberal, John Rawls, with the thought of the great process philosophers, Alfred North Whitehead and Charles Hartshorne. He shows that political liberalism is intimately linked with process philosophy, renaming it 'process liberalism'.